SIMIRALITAS PENDEKATAN PEMBELAJARAN AZ-ZARNUJI DAN KECERDASAN EMOSIONAL DANIEL GOLEMAN - Ahmad Solihin (Al-Hasanah : Jurnal Pendidikan Agama Islam, 2023)
Until now intellectuals are still regarded as the only potential of a person in achieving the success he wants. Unlike the case with emotional as a potential that is considered to hinder achieving success and adversely affect one's individual and social life. In 1990, a theory was found that emotions that humans have from birth, if managed properly, will direct a person to achieve success in his life as an individual and socially. The success of emotional management cannot be separated from the accuracy of the methods and approaches used. Learning methods and approaches can change patterns of thinking and behaving in achieving learning success. This study aims to find a similar approach to the success of learning Az-Zarnuji and Goleman. This study uses a qualitative descriptive method with similarity analysis through primary data sources, namely the book of Ta'lim al-Muta'allim by Burhanul Islam az-Zarnuji and Emotional Intelligence by Daniel Goleman. Meanwhile, the secondary data includes several analytical works on educational thinking about the terms and ethics of az-Zarnuji's learning and learning, as well as several analytical works on Goleman's emotional intelligence. The results of this study include the existence of similarity in achieving learning success through a serious and continuous approach to emotional management so that it creates skills in accepting and adapting to new situations.